Ambiphilic Al−Cu Bonding - Liu, Han‐Ying (Angew Chem Int Ed Engl, 2021)
Copper‐alumanyl complexes, [LCu‐Al(SiN(Dipp))], where L=carbene=NHC(iPr) (N,N′‐diisopropyl‐4,5‐dimethyl‐2‐ylidene) and (Me2)CAAC (1‐(2,6‐diisopropylphenyl)‐3,3,5,5‐tetramethyl‐pyrrolidin‐2‐ylidene) and featuring unsupported Al−Cu bonds, have been prepared. Divergent reactivity observed with carbodiimides and CO(2) implies an ambiphilicity in the Cu–Al interaction that is dependent on the identity of the carbene co‐ligand.